Bourgain-Brezis-Mironescu convergence via Triebel-Lizorkin spaces - Brazke, Denis; Schikorra, Armin; Yung, Po-Lam (Calculus of variations and partial differential equations, 2023)
We study a convergence result of Bourgain-Brezis-Mironescu (BBM) using Triebel-Lizorkin spaces. It is well known that as spaces Ws,p = Fs p,p, and H1,p = F1 p,2. ...
Online veröffentlicht am 24. Dezember 2022
Gesehen am 30.11.2023